Development of an Algorithm for Volumetric Reconstruction and Estimation of the Center of Mass of Solid Cohesive in Environments with Suspended Particles - Urrea-Onate, E; Kern-Molina, J; Quiroz-Moreno, J (Seventh Sense Research Group, 2023)
Volumetric reconstruction is a research niche that has attracted attention due to the large number of applications. There are several techniques to extract a point cloud from a scene, but stereo vision is the most recognized technique. Volumetric reconstruction is a research niche that has attracted attention during the last decade due to its many applications. There are several techniques to extract a point cloud from a scene, but the most recognized technique is stereo vision. Stereo vision uses two images of a set to calculate the distance of the objects from the cameras; however, in most reviewed works, this occurs in clean environments and with controlled lighting. This paper presents an algorithm capable of estimating a point cloud of some object in cloudy environments with suspended particles to subsequently approximate the center of mass of the entity for mining comminution applications. © 2023 Seventh Sense Research Group.